The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3797/scipharm.1204-26
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anti-Quorum Sensing Activity for Some Ornamental and Medicinal Plants Native to Egypt

Abstract: This study investigated the effects of some plant extracts on the bacterial communication system, expressed as quorum sensing (QS) activity. Quorum sensing has a directly proportional effect on the amount of certain compounds, such as pigments, produced by the bacteria. Alcohol extracts of 23 ornamental and medicinal plants were tested for anti-QS activity by the Chromobacterium violaceum assay using the agar cup diffusion method. The screening revealed the anti-QS activity of six plants; namely the leaves of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The extract was tested for the stated activity by Chromobacterium violaceum assay using the agar cup diffusion method. The extract of olives was not found active for antiquorum sensing activity [ 176 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…The extract was tested for the stated activity by Chromobacterium violaceum assay using the agar cup diffusion method. The extract of olives was not found active for antiquorum sensing activity [ 176 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Hence, inhibition of these signaling molecules hinders the pathogenicity of P. aeruginosa, and could be used for prevention or treatment of its infections Several plants have QS inhibiting activities. Medicinal plants 6 and edible plants 7 exhibited QSI effects. Also, Streptomyces coelicoflavus isolated from soil microbiota produced 1 H-pyrrole-2-carboxylic acid with QSI effect 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the components of burdock leaf exhibit high antibacterial activity (Zaki et al . ; Lou et al . ).…”
Section: Introductionmentioning
confidence: 99%